The role of oxidative stress in Brachiaria decumbens toxicity in sheep - Assumaidaee, Ajwad Awad Mohammed; Saad, Mohd Zamri; Sabri, Jasni; Mohamed Mustapha, Noordin (Universiti Putra Malaysia Press, 2010)
In an attempt to elucidate potential time-dependent oxidative stress mechanisms associated with Brachiaria decumbens toxicity in sheep, selected blood malondialdehyde (MD), as peroxidation tissue function biomarker and tissue morphology, were assessed. Six young adult Wiltshire cross bred ram were acclimatized for 3 weeks, where ivermectin injection and liver and kidney function tests were done. Blood samples were collected during the pre-treatment, namely on 3rd, 5th, 7th, 9th, and 11th days of continuous feeding of Brachiaria. Meanwhile, clinical signs were monitored and sheep were euthanised on the 7th, 9th, and 11th day, where a post-mortem was performed and relevant tissues were sampled. Results revealed that plasma thiobarbituric acid reactive substances (TBARS), serum (bilirubin total and conjugated, AST, GGT, urea, and creatinine) were significantly (p<0.05) increased, whereas total antioxidant potential was decreased (p<0.05) in a time dependant manner. Continuous B. decumbens feeding induced a time dependent appearance of jaundice, photosensitization, and subcutaneous oedema. Unique intracytoplasmic accumulation of Schmorl's positive greenish lipofuscin granules were observed primarily within the centrilobular hepatocytes and Kupffer cells. This may serve as a histochemical oxidative biomarker in the liver, kidney, brain, and skin. Taken together, this study shows that oxidative stress plays a major role in B. decumbens toxicity.